2005
DOI: 10.1007/s11095-005-6248-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in Vitro Evaluation of a Novel Chitosan–Glutathione Conjugate

Abstract: Because of the improved mucoadhesive and cohesive properties, and the strong permeation-enhancing effect of the chitosan-GSH conjugate/GSH system, the novel thiolated chitosan seems to represent a promising multifunctional excipient for various drug delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 23 publications
1
73
2
Order By: Relevance
“…GSH is a tripeptide with high conformational flexibility and is susceptible to oxidation and disulfide bond formation. 24 All thiolated chitosans revealed a higher amount of total sulfhydryl groups in comparison with free-thiol groups. It can be shown that the formation of intraand/or intermolecular disulfide bonds is possible.…”
Section: Discussionmentioning
confidence: 93%
“…GSH is a tripeptide with high conformational flexibility and is susceptible to oxidation and disulfide bond formation. 24 All thiolated chitosans revealed a higher amount of total sulfhydryl groups in comparison with free-thiol groups. It can be shown that the formation of intraand/or intermolecular disulfide bonds is possible.…”
Section: Discussionmentioning
confidence: 93%
“…Thiolated chitosan was prepared with covalent attachment of reduced glutathione to different molecular weight of chitosan according to the slightly modified method described by Atyabi et al and Kafedjiiski et al as follows: 5,27 One gram of chitosan was dispersed in 50 mL demineralized water by stirring, then 10 mL HCl (1 mol/L) was added and finally dissolved by the addition of demineralized water to obtain a 1% (w/v) polymer solution. The pH was adjusted to 6.0 by the addition of NaOH (5 mol/L).…”
Section: Chitosan Thiolationmentioning
confidence: 99%
“…Thiolated chitosan derivatives, such as chitosan-thioglycolic acid, chitosan-cysteine, can be obtained by reactions between amino groups of chitosan and reagents containing sulfhydryl groups (Jain et al 2013;Kast and Bernkop-Schnurch 2001;Wang et al 2009). The enhanced mucoadhesion may be attributed to the interactions between sulfhydryl and cysteine-rich subdomains of mucus layer (Kafedjiiski et al 2005). Mucoadhesion of thiolated chitosan is affected by its degree of thiolation (Roldo et al 2004).…”
Section: Chitosan Derivativesmentioning
confidence: 99%